Aural simulacra: The signal's path to metamorphosis. Issue 2 (1st June 2017) - Messinezis, Luc
Hyper-reality has often been described as the inability of perception to identify and distinguish reality from a simulation of reality. Modern thinkers and scholars such as Umberto Eco and Jean Baudrillard have elaborated extensively on the subject and the effect of simulations within a variety of aspects of modern life. When it comes to auditory arts and research, even though the influence of simulations may be evident, it seems to have been overlooked. With this article, I intend to scrutinize 'aural simulacra'. During the last two centuries, the audio signal has passed through various stages of transformation; it has mutated following the rhythm of an era marked by technological advancement and a globalized plethora of ideas. For example, the phenomenon of schizophonia has rendered possible the detachment of sounds from their original source and reproducing them within a variety of different contexts. Reproductive media in their turn have evolved from carved discs to magnetic tapes and from optical means to digital abyssal clouds, matrixes of ones and zeroes promoting endless expressive possibilities. In addition, innovative diffusion methods are being introduced and virtual reality technologies have started to populate the scene. Despite the debate on whether the medium may or may not be the message, it adds to it; it acts as a catalyst to an evolutionary reaction. But what happens to the signal itself? Is it transcending to a different dimension of existence?Treating the signal as a sign, together with practice-based research, may delineate the importance of its conceptual metamorphosis and the ramifications it has for creative processes and the audience's engagement with the sound artwork. With this article, I intend to examine the sign orders in relation to auditory reality and authenticity, the signal's change as it may belong to the sacramental order, the order of maleficence, the order of sorcery or find itself outside of the orders of the heard as pure simulacrum. The acknowledgement of the aural simulacrum and the study of the signal's path towards it may affect our understanding of sonic arts practice, the mediumship of the listener and related areas of research. More specifically subjects such as acoustic ecology, composition but also historical auditory research are scholarly fields that are expected to be influenced, initiating further dialogue, critical analysis and providing the foundation for further interdisciplinary research and new creative processes.